Understanding the Link between Literacy and Numeracy Skills among Primary Pupils - Jabanes, Agripina; Futalan, Maria Chona (Journal of Interdisciplinary Perspectives, 2025)
This study examined the relationship between literacy and numeracy skills among Grade 3 learners. A total of 340 learners from 21 schools in the Valencia District were selected using a systematic sampling method. Informed consent was obtained from all participants, and strict measures were implemented to ensure data confidentiality. The study employed a descriptive-correlational design and utilized standardized EGRA and EGMA testing tools. Percentages, means, and the Chi-Square Test were used for statistical analysis. Findings revealed that approximately 20% of the learners were non-readers, while 30% were non-numerate. The study also established a significant relationship between learners' foundational literacy and their numeracy skills. Data on foundational literacy showed that female learners, those excelling in English and Math, learners from higher-income families, and those with educated parents achieved higher scores. For numeracy skills, only English and Math performance were significantly linked to learners' math abilities. These findings underscore the importance of targeted educational planning and interventions that support disadvantaged groups and enhance core subject skills to improve overall literacy and numeracy outcomes.